Occupier's Liability after See Toh: Change, Uncertainty and Complexity - LOW, Kee Yang (Institutional Knowledge at Singapore Management University, 2013)
With the recent Court of Appeal decision in See Toh (C.A.), the Singapore law on occupiers' liability has undergone a sea change. There are two obvious changes. The first is that there is no longer a distinction between invitees and licensees; the law accords them the same protection. The second is that occupiers' liability is no longer a separate tort; it is now subsumed under the tort of negligence. However, the full implications of See Toh (C.A.) are more far-reaching and profound than a casual reading of this landmark decision might suggest. The SeeToh (C.A.) decision potentially upgrades the protection and rights of unlawful entrants. The Gordian knot of common law occupiers' liability has indeed been cut; but as Singapore courts set out to conquer this legal realm, with all its problems and complexities, it would be naive to expect the ride to be a smooth and easy one.